Is Sustainability Report Disclosure Implemented Properly? (A Case Study of Companies Listed in Sri-Kehati Index) - Taufik Akbar; Edi Murdiyanto (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This study aims to identify sustainability reports conducted by companies listed in the Sri-Kehati index. This is a qualitative research and the GRI standards are a reference in disclosure. The result of the research shows that there is no guarantee that companies listed in the Sri-Kehati index will make a complete disclosure, especially compliance with GRI standards. Too many aspects or reporting standards should be implemented following global standards such as GRI. Based on SRDI calculation, shows that AKR Corporindo, Perusahaan Gas Negara (PGN), Bank BTN, Cikarang Listrindo, Indofood Sukses Makmur, and Semen Indonesia are classified as companies that make disclosures with the highest GRI index. Meanwhile, companies with low disclosures include Bumi Serpong Damai, Telkom, Jasa Marga, Sido Muncul, PP (Persero), Kalbe Farma, and Adi Sarana Armada.